Carbon electrode perovskite battery and thermoelectric power generation laminated device and preparation method thereof
By designing carbon electrode perovskite batteries and temperature differential power generation stacked devices in perovskite solar cells, using infrared energy, the problems of short cut-off absorption wavelength and low infrared band utilization are solved, and photovoltaic and photoelectric conversion are improved Efficiency, achieving high-performance perovskite solar cells.
Patent Information
- Application Number
- CN202310861880.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-14
AI Technical Summary
The cutoff absorption wavelength of the light absorbing layer of the perovskite solar cell leads to a low infrared band utilization, reducing photocurrent and photovoltaicity, and the working temperature on the carbon electrode side is high, which is not conducive to the device's photoelectric conversion efficiency.
A carbon electrode perovskite battery and temperature differential power generation stacked device was designed, including transparent conductive glass, electron transport layer, mesoporous layer, perovskite absorber layer, carbon electrode photothermal film composite layer and temperature differential power generation device, through optimization The layer structure and material combination make full use of infrared energy and improve photoelectric conversion efficiency.
The photovoltage and photoelectric conversion efficiency of perovskite batteries are improved, and the problems of short cut-off absorption wavelength of the light absorbing layer and low infrared band utilization are solved, which maximizes the heat generated by the carbon electrode layer and improves the overall performance of the device.
Smart Images

Figure CN119317301A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of perovskite solar cells, and in particular relates to a carbon electrode perovskite cell and a temperature difference power generation stacked device and a preparation method thereof. Background Art
[0002] Perovskite solar cells have developed rapidly since 2009, and the photoelectric conversion efficiency of the devices has been rising. The highest certified efficiency of the cells prepared in the laboratory is currently as high as 26%. In recent years, carbon electrode perovskite solar cells have received extensive attention due to their low preparation cost, simple preparation process and good device stability. However, carbon electrode perovskite solar cells without hole transport layer have the following problems: 1) Due to the short cutoff absorption wavelength of the perovskite light absorption layer, the infrared band utilization is low, which reduces the photocurrent and photovoltage; 2) The infrared energy loss causes the operating temperature of the carbon electrode side of the device to be high, which is not conducive to the photoelectric conversion efficiency of the device. Summary of the invention
[0003] In view of the above problems, the present invention discloses a carbon electrode perovskite battery and a thermoelectric power generation stacked device, comprising: a transparent conductive glass, an electron transport layer, a mesoporous layer, a perovskite light absorption layer, a carbon electrode photothermal film composite layer, a thermoelectric power generation device and an electrode layer;
[0004] The electron transport layer, the mesoporous layer, the perovskite light absorption layer, the carbon electrode photothermal film composite layer, and the temperature difference power generation device are arranged in sequence from bottom to top on the conductive surface of the transparent conductive glass;
[0005] The electrode layer is arranged on the conductive surface of the transparent conductive glass and is not in contact with the electron transport layer, the mesoporous layer and the perovskite light absorption layer;
[0006] The thickness of the perovskite light-absorbing layer is 650-800 nm.
[0007] Furthermore, the transparent conductive glass is fluorine-doped tin oxide, has a thickness of 1.1 to 2.2 mm, a square resistance of <8Ω, a light transmittance of ≥79%, and a haze of <4%.
[0008] Furthermore, the electron transport layer is prepared using titanium tetrachloride aqueous solution as a precursor, and the concentration of the titanium tetrachloride aqueous solution is 120mM to 260mM;
[0009] The thickness of the electron transport layer is 18 to 31 nm;
[0010] The total thickness of the mesoporous layer and the electron transport layer is 42-68 nm.
[0011] Furthermore, the perovskite light-absorbing layer is a Cs-FA-MA polyvalent cation structure.
[0012] Furthermore, the carbon electrode photothermal film composite layer comprises a carbon electrode layer and a photothermal film layer;
[0013] The thickness of the carbon electrode photothermal film composite layer is 16 to 30 um.
[0014] Furthermore, the temperature at which the thermoelectric power generation device achieves maximum conversion efficiency is less than 75°C.
[0015] The present invention also discloses a method for preparing a carbon electrode perovskite battery and a temperature difference power generation stacked device, comprising the following steps:
[0016] Processing of transparent conductive glass;
[0017] An electron transport layer and a mesoporous layer are sequentially prepared on the conductive surface of the treated transparent conductive glass;
[0018] Spin coating a perovskite precursor on the surface of the mesoporous layer to obtain a perovskite light absorbing layer;
[0019] A carbon electrode layer is prepared on the surface of the perovskite light-absorbing layer, the electrode layer is welded to one end of the conductive surface of the transparent conductive glass, and a photothermal film layer is sputtered on the surface of the carbon electrode layer; wherein the carbon electrode photothermal film composite layer includes the carbon electrode layer and the photothermal film layer;
[0020] The thermoelectric power generation device is bonded to the photothermal film layer to obtain a carbon electrode perovskite cell and a thermoelectric power generation stacked device.
[0021] Furthermore, the specific steps of sequentially preparing the electron transport layer and the mesoporous layer on the treated conductive surface of the transparent conductive glass are as follows:
[0022] The treated transparent conductive glass is immersed in a titanium tetrachloride aqueous solution, placed in an 80°C oven, kept warm for 58 to 62 minutes, washed and dried to obtain an electron transport layer, and then a titanium dioxide mesoporous precursor solution is spin-coated on the surface of the electron transport layer, heated and dried, and placed in a muffle furnace at 500 to 520°C, kept warm for 20 to 30 minutes to obtain a mesoporous layer;
[0023] Wherein, the concentration of the titanium tetrachloride aqueous solution is 120mM to 260mM;
[0024] The concentration of the titanium dioxide mesoporous precursor solution is 10-20M.
[0025] Furthermore, the specific steps of spin coating the perovskite precursor on the surface of the mesoporous layer to obtain the perovskite light absorbing layer are as follows:
[0026] Dissolving the perovskite raw material in a mixed solvent of DMF and DMSO to prepare a perovskite precursor solution;
[0027] The mesoporous layer is treated with low-temperature plasma, and then a perovskite precursor solution is spin-coated on the surface of the mesoporous layer, and then annealed at 155-176° C. for 22-28 minutes to obtain a perovskite light-absorbing layer;
[0028] Among them, the volume ratio of DMSO to DMF is 1:3-4;
[0029] The concentration of the perovskite precursor solution is 1.4-1.6M;
[0030] The spin coating conditions are 900-1200 rpm, 9-10 s, 4500-5000 rpm, 16-18 s; wherein, during the 10th to 14th s of high-speed rotation, 120-165 uL of anisole is rapidly added dropwise;
[0031] The band gap of the perovskite light-absorbing layer is 1.48 to 1.56 eV.
[0032] Furthermore, the specific steps of preparing a carbon electrode layer on the surface of the perovskite light-absorbing layer, welding the electrode layer on one end of the conductive surface of the transparent conductive glass, and sputtering a photothermal film layer on the surface of the carbon electrode layer are as follows:
[0033] A carbon electrode layer is scraped onto the surface of the perovskite light-absorbing layer and annealed at 100-125°C for 20-35 minutes;
[0034] Welding an electrode layer at one end of the conductive surface of the transparent conductive glass;
[0035] In 5~6×10 -6 mtorr vacuum, Ar / N 2 / O 2 Under the environment, ZrNbMo is prepared by radio frequency sputtering and Al is prepared by direct current sputtering on the surface of the carbon electrode layer to obtain a ZrNbMo-Al-N high entropy photothermal film layer.
[0036] Compared with the prior art, the embodiments of the present invention have at least the following advantages:
[0037] 1. The carbon electrode perovskite cell and the temperature difference power generation stacked device of the present invention make full use of infrared energy, solve the problems of short cut-off absorption wavelength of the light-absorbing layer of the carbon electrode perovskite device and low infrared band utilization, and improve the photovoltage of the perovskite cell and the photoelectric conversion efficiency of the device;
[0038] 2. Stacking with thermoelectric power generation devices can maximize the use of heat generated by the carbon electrode layer and improve the photoelectric conversion efficiency of the stacked devices.
[0039] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 A schematic structural diagram of a carbon electrode perovskite cell and a thermoelectric power generation stack device according to an embodiment of the present invention is shown;
[0042] Figure 2 A cross-sectional SEM image of a carbon electrode perovskite cell according to an embodiment of the present invention is shown;
[0043] Figure 3 The photoelectric conversion efficiency of the carbon electrode perovskite cell according to the embodiment of the present invention is shown;
[0044] Figure 4 The photoelectric conversion efficiency of the carbon electrode perovskite cell and the thermoelectric power generation stack device according to an embodiment of the present invention is shown;
[0045] Figure 5 A SEM image of a carbon electrode photothermal film composite layer according to an embodiment of the present invention is shown.
[0046] Figure numerals: 1. transparent conductive glass; 2. electron transport layer; 3. perovskite light absorption layer; 4. carbon electrode photothermal film composite layer; 5. thermoelectric power generation device; 6. electrode layer. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Figure 1 The schematic diagram of the structure of the carbon electrode perovskite battery and the thermoelectric power generation stack device according to the embodiment of the present invention is shown. Figure 1 As shown, a carbon electrode perovskite battery and a thermoelectric power generation stacked device proposed in the present invention comprises: a transparent conductive glass 1, an electron transport layer 2, a mesoporous layer, a perovskite light absorption layer 3, a carbon electrode photothermal film composite layer 4, a thermoelectric power generation device 5 and an electrode layer 6;
[0049] The electron transport layer 2, the mesoporous layer, the perovskite light absorption layer 3, the carbon electrode photothermal film composite layer 4, and the thermoelectric power generation device 5 are arranged on the conductive surface of the transparent conductive glass 1 in sequence from bottom to top;
[0050] The electrode layer 6 is arranged on the conductive surface of the transparent conductive glass 1 and is not in contact with the electron transport layer 2, the mesoporous layer, the perovskite light absorption layer 3, the carbon electrode photothermal film composite layer 4, and the thermoelectric power generation device 5;
[0051] The thickness of the perovskite light absorption layer 3 is 650-800 nm, which can ensure that the perovskite light absorption layer 3 fully absorbs photon energy while achieving the separation and transmission rate of photogenerated carriers.
[0052] The carbon electrode perovskite cell and the temperature difference power generation stacked device of the present invention make full use of infrared energy, solve the problems of short cut-off absorption wavelength of the light absorbing layer of the carbon electrode perovskite device and low infrared band utilization, and improve the photovoltage of the perovskite cell and the photoelectric conversion efficiency of the device.
[0053] In some embodiments, the transparent conductive glass 1 is fluorine-doped tin oxide (FTO), has a thickness of 1.1-2.2 mm, a square resistance of <8Ω, a transmittance of ≥79%, and a haze of <4%.
[0054] The smaller square resistance of the transparent conductive glass 1 ensures the conductivity and is conducive to the rapid transmission of electrons; the transmittance and haze can ensure that more light can pass through the FTO and be absorbed by the perovskite light absorption layer 3.
[0055] In some embodiments, the electron transport layer 2 is prepared by chemical bath deposition, specifically by using titanium tetrachloride aqueous solution as a precursor, and the concentration of the titanium tetrachloride aqueous solution is 120mM to 260mM;
[0056] The thickness of the electron transport layer 2 is 18 to 31 nm; this thickness can ensure the coverage, electron transport and extraction rate of the electron transport layer 2;
[0057] The total thickness of the mesoporous layer and the electron transport layer 2 is 42-68 nm.
[0058] Exemplarily, the electron transport layer 2 is titanium dioxide.
[0059] In some embodiments, the perovskite light absorbing layer 3 is a Cs-FA-MA polyvalent cation structure.
[0060] The mesoporous layer is prepared by spin coating. Exemplarily, the material of the mesoporous layer is titanium dioxide.
[0061] In some embodiments, the carbon electrode photothermal film composite layer 4 includes a carbon electrode layer and a magnetron sputtered high entropy nitride photothermal film layer;
[0062] The thickness of the carbon electrode photothermal film composite layer 4 is 16-30 um.
[0063] Among them, the carbon electrode layer is prepared by scraping method; the photothermal film layer is prepared by magnetron sputtering method, and can also be prepared by hydrothermal method, ball milling method and other methods.
[0064] In hole-free carbon-based perovskite solar cells, the absorption and extinction effects of porous carbon electrodes include extinction that causes loss of photoelectrons without secondary light reflection, collision of hot carriers generated by carbon electrode absorption that reduces the number of photoelectrons, and interaction between regional heat and the perovskite carbon electrode interface. The carbon electrode photothermal film composite layer 4 is constructed to realize the perovskite-thermoelectric power generation stacked integrated device with shared electrodes, and the integrated device is more compact and lightweight. At the same time, the absorption and heat generation of photons in the mid-infrared band by the shared electrode are clarified, the coupling relationship between light and heat performance is improved, the mechanism of electron transmission and heat conduction is formed, and finally the multi-carrier coupling interaction mechanism between photons (light energy)-phonons (heat energy)-electrons (electrical energy) is established. On this basis, a low-cost, easy-to-prepare, high-performance perovskite solar cell is realized.
[0065] In some embodiments, the temperature at which the thermoelectric power generation device 5 obtains the maximum conversion efficiency is less than 75°C.
[0066] Considering the operating temperature of the carbon electrode side of the perovskite device, the top temperature difference power generation device 5 uses a low temperature device (<100°C). 2 Te 3 , MgAgSb, PbSe, AgCuTe, etc. The thermoelectric power generation device 5 is not limited to the above materials, but requires the temperature to obtain the maximum conversion efficiency is less than 75°C.
[0067] Based on the above-mentioned carbon electrode perovskite battery and thermoelectric power generation stacked device, the present invention also discloses a method for preparing the carbon electrode perovskite battery and the thermoelectric power generation stacked device, comprising the following steps:
[0068] Treating the transparent conductive glass 1: washing the transparent conductive glass 1 with water, ethanol, and isopropanol for 25 to 30 minutes, drying it, and performing low-temperature plasma treatment;
[0069] An electron transport layer 2 and a mesoporous layer are sequentially prepared on the conductive surface of the treated transparent conductive glass 1;
[0070] Spin coating the perovskite precursor on the surface of the mesoporous layer to obtain the perovskite light absorbing layer 3;
[0071] A carbon electrode layer is prepared on the surface of the perovskite light-absorbing layer 3, an electrode layer 6 is welded to one end of the conductive surface of the transparent conductive glass 1, and a photothermal film layer is sputtered on the surface of the carbon electrode layer; wherein the carbon electrode photothermal film composite layer 4 includes a carbon electrode layer and a photothermal film layer;
[0072] The hot end of the thermoelectric power generation device 5 is bonded to the photothermal film layer by curing carbon slurry to realize shared electrodes and ensure bonding strength and good heat conduction to form a series structure, thereby obtaining a carbon electrode perovskite cell and a thermoelectric power generation stacked device.
[0073] In some embodiments, the specific steps of sequentially preparing the electron transport layer 2 and the mesoporous layer on the conductive surface of the treated transparent conductive glass 1 are as follows:
[0074] The treated transparent conductive glass 1 is immersed in a titanium tetrachloride aqueous solution, placed in an oven at 80°C, kept warm for 58-62 minutes, washed and dried to obtain an electron transport layer 2, and then a titanium dioxide mesoporous precursor solution with a particle size of 30 nm is spin-coated on the surface of the electron transport layer 2 at 4000-4600 rpm for 20 seconds, and heated and dried at 120°C, and then placed in a muffle furnace at 500-520°C, kept warm for 20-30 minutes (preferably, kept warm for 30 minutes), to obtain a mesoporous layer;
[0075] Wherein, the concentration of the titanium tetrachloride aqueous solution is 120mM to 260mM;
[0076] The concentration of the titanium dioxide mesoporous precursor solution is 10-20M.
[0077] The prepared electron transport layer 2 and the mesoporous layer are placed in a muffle furnace for annealing, which can remove the organic solvent on the one hand and increase the crystallinity of titanium dioxide on the other hand.
[0078] In some embodiments, the specific steps of spin coating the perovskite precursor on the surface of the mesoporous layer to obtain the perovskite light absorbing layer 3 are as follows:
[0079] The perovskite raw materials are dissolved in a mixed solvent of DMF and DMSO to prepare a perovskite precursor solution; illustratively, the perovskite raw materials are CsI, FAI, PbI 2 and MACl; the perovskite precursor solution is Cs-FA-MAPbI 3 structure;
[0080] The mesoporous layer was subjected to low-temperature plasma treatment at 300 W for 120 s, and then a perovskite precursor solution was spin-coated on the surface of the mesoporous layer, and then annealed at 155 to 176° C. for 22 to 28 min in a glove box to obtain a perovskite light-absorbing layer 3;
[0081] Preferably, the annealing temperature is 168°C;
[0082] The general structural formula of the perovskite light absorbing layer 3 is Cs 1-x-y FA x MA y PbI 3 , x: 0.73~0.88, y: 0.005~0.015, the perovskite in this composition range has a suitable band gap, a longer carrier diffusion length, high-quality film quality, higher stability and photoelectric properties.
[0083] The volume ratio of DMSO to DMF is 1:3-4; the solvent prepared according to this ratio can not only dissolve the solute of perovskite more fully, but also DMSO and PbI 2 The coordination of MgO can effectively delay the crystallization of perovskite and improve the quality of the film;
[0084] The concentration of the perovskite precursor solution is 1.4-1.6M;
[0085] The spin coating conditions are 900-1200 rpm, 9-10 s, 4500-5000 rpm, 16-18 s; wherein, during the 10th to 14th second of high-speed rotation, 120-165 uL of anisole is rapidly added dropwise; preferably, the amount of anisole added is 150 uL;
[0086] The band gap of the perovskite light absorbing layer 3 is 1.48 to 1.56 eV.
[0087] In some embodiments, the specific steps of preparing a carbon electrode layer on the surface of the perovskite light absorbing layer 3, welding an electrode layer 6 on one end of the conductive surface of the transparent conductive glass 1, and sputtering a photothermal film layer on the surface of the carbon electrode layer are as follows:
[0088] A carbon electrode layer is scraped onto the surface of the perovskite light absorbing layer 3 and annealed at 100-125° C. for 20-35 min;
[0089] Welding an electrode layer 6 at one end of the conductive surface of the transparent conductive glass 1;
[0090] In 5~6×10 -6 mtorr vacuum, Ar / N 2 / O 2 Under the environment, the co-sputtering method is used to prepare ZrNbMo by radio frequency sputtering and Al by DC sputtering on the surface of the carbon electrode layer to obtain a ZrNbMo-Al-N high entropy photothermal film layer. The thickness of the carbon electrode photothermal film composite layer 4 is 16 to 30 um.
[0091] Perovskite solar cells have a high light absorption coefficient, but the utilization rate of the infrared band is low. At the same time, the unused infrared band is absorbed by the carbon electrode layer, and the heat generated will damage the device efficiency. The preparation method of the present invention provides a new idea for improving the conversion efficiency of low-cost and easy-to-prepare carbon electrode perovskite solar cells, and also promotes the commercial development of perovskite cells.
[0092] Example 1
[0093] like Figure 1 As shown, the structure of the two-terminal carbon electrode perovskite battery / thermoelectric power generation stacked device is from bottom to top: conductive substrate FTO, titanium dioxide electron transport and mesoporous co-deposition layer, perovskite light absorption layer 3, carbon electrode photothermal film composite layer 4 and thermoelectric power generation device 5. Its preparation steps are as follows:
[0094] At one end of the conductive substrate FTO, a rectangular insulating area is etched by laser to prepare for the subsequent scraping of the carbon electrode layer. The remaining functional layers are all carried out on the conductive substrate FTO.
[0095] The conductive substrate FTO was ultrasonically cleaned with deionized water, isopropanol, and ethanol for 25 minutes, and then dried with an air gun. It was placed in a low-temperature plasma treatment instrument with a treatment condition of 300W for 300s and oxygen gas with a purity of 99.9%;
[0096] After treatment, the conductive substrate FTO was immersed in a titanium tetrachloride aqueous solution with a concentration of 180 mM, sealed with plastic wrap, and placed in an 80°C oven for 60 minutes. After being taken out, it was immediately washed with deionized water until the surface of the conductive substrate FTO was obviously unchanged. After that, it was heated on a heating plate at 120°C for 10 minutes and cooled to room temperature to obtain a titanium dioxide electron transport layer 2.
[0097] Commercial titanium dioxide slurry (Dyesol, 30NR-D) was mixed with ethanol at a mass ratio of 1:6.6. After stirring for 20 hours, 120uL was added dropwise to the titanium dioxide electron transport layer 2 at a spin coating speed of 4000rpm for 20s. Then, it was placed in a 515℃ muffle furnace for co-annealing and kept warm for 30min to obtain a mesoporous layer. The thickness of the electron transport layer 2 was 25nm; the total thickness of the electron transport layer 2 and the mesoporous layer was 56nm.
[0098] Weigh 49.3 mg of CsI (cesium iodide) powder, 139 mg of formamidine iodide (FAI) powder, 6.8 mg of methylamine chloride (MACl) powder, 462 mg of lead iodide (PbI 2 ) powder, pipette 145 μl of dimethyl sulfoxide (DMSO) and 500 μl of N,N-dimethylformamide (DMF), mix and shake for 10 h, and filter with a 0.22 μm polytetrafluoroethylene filter to form Cs0.19 FA 0.8 MA 0.01 PbI 3 Perovskite precursor solution.
[0099] The two-step anti-solvent spin coating method was used, with low-speed rotation for 10 s at 1000 rpm and high-speed rotation for 18 s at 4500 rpm. At the 12th s of high-speed rotation, 150 μl of anisole anti-solvent was added dropwise, and annealing was performed at 168 °C in the glove box for 26 min to prepare Cs 0.19 FA 0.8 MA 0.01 PbI 3 The perovskite film has a band gap of 1.49 eV. The cross-sectional SEM image is shown in Figure 2 As shown, the thickness of the perovskite light absorbing layer 3 is 780 nm.
[0100] The carbon slurry was scraped onto the FTO etched area of the conductive substrate and cured at 120°C for 20 min.
[0101] The perovskite light-absorbing layer 3 on the other side of the insulating region parallel to the conductive substrate FTO is scraped off, and metal indium (as the negative electrode) is spread flat on the conductive substrate FTO region using an ultrasonic welder to produce a carbon electrode perovskite solar cell without a hole transport layer.
[0102] The photoelectric conversion efficiency of the device (forward scanning efficiency and reverse scanning efficiency) is as follows: Figure 3 shown.
[0103] Example 2
[0104] The preparation process of carbon electrode perovskite solar cell is the same as that of Example 1, and the device efficiency is shown in Figure 4 .
[0105] Preparation of carbon electrode photothermal film composite layer 4. At 5.2×10 -6 mtorr vacuum, with Ar / N 2 / O 2 Gas, the ratio is 1:1.2:0.06, using the co-sputtering method, RF sputtering to prepare ZrNbMo, the power is 285W; DC sputtering to prepare Al, the power is 280W. The ZrNbMo-Al-N high entropy photothermal film is sputtered onto the carbon electrode layer. The carbon electrode photothermal film composite layer 4 is 18um thick, and the cross-sectional SEM is as follows Figure 5 shown.
[0106] The negative electrode (hot end) of the thermoelectric power generation device 5 and the carbon electrode photothermal film composite layer 4 are bonded with carbon slurry, and kept at 120°C for 15 minutes to realize shared integrated electrodes, completing the preparation of the entire two-terminal carbon electrode perovskite battery and the thermoelectric power generation stack device. The cold end of the thermoelectric power generation device 5 is used as the positive electrode.
[0107] In this example, a carbon electrode photothermal film composite layer 4 and a shared carbon electrode layer are prepared to prepare a two-terminal carbon electrode perovskite cell and a temperature difference power generation stacked device. The device efficiency is as follows Figure 4 The specific parameters are shown in Table 1. The open circuit voltage of the stacked device is increased from 1.01V of the perovskite battery to 1.26V, and the photoelectric conversion efficiency is increased from 17.2% to 21.9%.
[0108] Table 1 Performance parameters of perovskite cells, thermoelectric devices and two-terminal carbon electrode perovskite / thermoelectric stack devices
[0109]
[0110] The two-terminal carbon electrode perovskite / thermoelectric power generation stacked device obtained in this embodiment makes full use of infrared energy, solves the problems of short cutoff absorption wavelength of the carbon electrode perovskite device's light-absorbing layer and low infrared band utilization, and improves the photovoltage of the perovskite cell and the photoelectric conversion efficiency of the device.
[0111] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A carbon electrode perovskite battery and a temperature difference power generation stacked device, characterized in that: include: Transparent conductive glass (1), an electron transport layer (2), a mesoporous layer, a perovskite light absorption layer (3), a carbon electrode photothermal film composite layer (4), a thermoelectric power generation device (5) and an electrode layer (6); The electron transport layer (2), the mesoporous layer, the perovskite light absorption layer (3), the carbon electrode photothermal film composite layer (4), and the temperature difference power generation device (5) are arranged in sequence from bottom to top on the conductive surface of the transparent conductive glass (1); The electrode layer (6) is arranged on the conductive surface of the transparent conductive glass (1) and is not in contact with the electron transport layer (2), the mesoporous layer and the perovskite light absorption layer (3); The thickness of the perovskite light-absorbing layer (3) is 650-800 nm.
2. The carbon electrode perovskite battery and thermoelectric power generation stacked device according to claim 1, characterized in that: The transparent conductive glass (1) is fluorine-doped tin oxide, has a thickness of 1.1-2.2 mm, a square resistance of less than 8Ω, a light transmittance of ≥79%, and a haze of less than 4%.
3. The carbon electrode perovskite battery and thermoelectric power generation stacked device according to claim 1, characterized in that: The electron transport layer (2) is prepared using a titanium tetrachloride aqueous solution as a precursor, and the concentration of the titanium tetrachloride aqueous solution is 120 mM to 260 mM; The thickness of the electron transport layer (2) is 18 to 31 nm; The total thickness of the mesoporous layer and the electron transport layer (2) is 42-68 nm.
4. The carbon electrode perovskite battery and thermoelectric power generation stacked device according to claim 2, characterized in that: The perovskite light-absorbing layer (3) is a Cs-FA-MA polyvalent cation structure.
5. The carbon electrode perovskite battery and thermoelectric power generation stacked device according to claim 1, characterized in that: The carbon electrode photothermal film composite layer (4) comprises a carbon electrode layer and a photothermal film layer; The thickness of the carbon electrode photothermal film composite layer (4) is 16 to 30 um.
6. The carbon electrode perovskite battery and thermoelectric power generation stacked device according to claim 1, characterized in that: The temperature at which the thermoelectric power generation device (5) achieves maximum conversion efficiency is less than 75°C.
7. A method for preparing a carbon electrode perovskite battery and a temperature difference power generation stacked device, characterized in that: The following steps are involved: Processing the transparent conductive glass (1); An electron transport layer (2) and a mesoporous layer are sequentially prepared on the conductive surface of the treated transparent conductive glass (1); Spin-coating a perovskite precursor on the surface of the mesoporous layer to obtain a perovskite light-absorbing layer (3); A carbon electrode layer is prepared on the surface of the perovskite light absorption layer (3), an electrode layer (6) is welded to one end of the conductive surface of the transparent conductive glass (1), and a photothermal film layer is sputtered on the surface of the carbon electrode layer; wherein the carbon electrode photothermal film composite layer (4) comprises a carbon electrode layer and a photothermal film layer; The thermoelectric power generation device (5) is bonded to the photothermal film layer to obtain a carbon electrode perovskite cell and a thermoelectric power generation stacked device.
8. The method for preparing the carbon electrode perovskite battery and the thermoelectric power generation stacked device according to claim 7, characterized in that: The specific steps of sequentially preparing the electron transport layer (2) and the mesoporous layer on the conductive surface of the treated transparent conductive glass (1) are as follows: The treated transparent conductive glass (1) is immersed in a titanium tetrachloride aqueous solution, placed in an oven at 80° C., kept warm for 58 to 62 minutes, washed and dried to obtain an electron transport layer (2), and then a titanium dioxide mesoporous precursor solution is spin-coated on the surface of the electron transport layer (2), heated and dried, and then placed in a muffle furnace at 500 to 520° C., kept warm for 20 to 30 minutes, to obtain a mesoporous layer; Wherein, the concentration of the titanium tetrachloride aqueous solution is 120mM to 260mM; The concentration of the titanium dioxide mesoporous precursor solution is 10-20M.
9. The method for preparing the carbon electrode perovskite battery and the thermoelectric power generation stacked device according to claim 7, characterized in that: The specific steps of spin coating the perovskite precursor on the surface of the mesoporous layer to obtain the perovskite light absorbing layer (3) are as follows: Dissolving the perovskite raw material in a mixed solvent of DMF and DMSO to prepare a perovskite precursor solution; The mesoporous layer is subjected to low-temperature plasma treatment, and then a perovskite precursor solution is spin-coated on the surface of the mesoporous layer, followed by annealing at 155-176° C. for 22-28 minutes to obtain a perovskite light-absorbing layer (3); Among them, the volume ratio of DMSO to DMF is 1:3-4; The concentration of the perovskite precursor solution is 1.4-1.6M; The spin coating conditions are 900-1200 rpm, 9-10 s, 4500-5000 rpm, 16-18 s; wherein, during the 10th to 14th s of high-speed rotation, 120-165 uL of anisole is rapidly added dropwise; The band gap of the perovskite light absorbing layer (3) is 1.48 to 1.56 eV.
10. The method for preparing the carbon electrode perovskite battery and the thermoelectric power generation stacked device according to claim 7, characterized in that: The specific steps of preparing a carbon electrode layer on the surface of the perovskite light absorbing layer (3), welding an electrode layer (6) on one end of the conductive surface of the transparent conductive glass (1), and sputtering a photothermal film layer on the surface of the carbon electrode layer are as follows: A carbon electrode layer is scraped onto the surface of the perovskite light absorbing layer (3), and annealed at 100 to 125° C. for 20 to 35 minutes; Welding an electrode layer (6) to one end of the conductive surface of the transparent conductive glass (1); In 5~6×10 -6 In a mtorr vacuum and Ar / N2 / O2 environment, ZrNbMo was prepared by radio frequency sputtering on the surface of the carbon electrode layer, and Al was prepared by direct current sputtering to obtain a ZrNbMo-Al-N high entropy photothermal film layer.